2021
DOI: 10.1093/ibd/izab039
|View full text |Cite
|
Sign up to set email alerts
|

Aging and IBD: A New Challenge for Clinicians and Researchers

Abstract: Evidence from recent epidemiological data suggests that the patient population with inflammatory bowel disease (IBD) is chronologically aging. As these individuals become older, cellular senescence leads to a state of chronic inflammation. This process, known as inflammaging, is thought to be closely linked with biological aging and may be upregulated within IBD. As a consequence, we see an increased risk of aging-related disorders within IBD. In addition, we see that frailty, which results from physiologic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 74 publications
(104 reference statements)
1
32
0
Order By: Relevance
“… 3 Meanwhile, as a protracted course of disease with no known cure and limited excess mortality, the prevalence of IBD is predominantly high in the elderly, accounting for approximately one-third of IBD patients. 4 …”
Section: Introductionmentioning
confidence: 99%
“… 3 Meanwhile, as a protracted course of disease with no known cure and limited excess mortality, the prevalence of IBD is predominantly high in the elderly, accounting for approximately one-third of IBD patients. 4 …”
Section: Introductionmentioning
confidence: 99%
“…38,39 Long-term ongoing chronic inflammation exacerbates the risk of cardiovascular disease, which could explain why the increased mortality was detected for the first time after 30 years of follow-up of the IBSEN study. 14,40 In patients with CD, male sex, diagnosis after 40 years of age and colonic disease result in higher mortality. This association was also observed in a comparable Danish cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Although treatments and clinical strategies have gradually improved, particularly with the emergence of tumour necrosis factor [TNF]-α inhibitors, the rising proportion of elderly patients poses new challenges. [14][15][16][17] For example, therapeutics that compromise the immune system may raise the risk of serious infections or malignancies in elderly patients. [18][19][20][21][22] Studies centered on elderly IBD patients repeatedly found increased mortality rates.…”
Section: Inflammatory Bowel Diseases [Ibd] Including Crohn's Diseasementioning
confidence: 99%
“…[154][155][156][157][158] Although chronological age and comorbidities are often used in risk stratification tools, recent data suggest that frailty might be a better comprehensive assessment of an individual's risk of adverse health outcomes. [159][160][161][162] The prevalence of frailty increases with age, and patients who are frail present with more comorbidities; however, advanced chronological age, multimorbidity, and frailty are not synonyms. 163 Proinflammatory cytokines have a role in the pathophysiology of frailty, which is particularly relevant to consider in chronic inflammatory diseases such as IBD.…”
Section: Frailty In Ibd Trialsmentioning
confidence: 99%